PENTINGNYA KETERAMPILAN PENGAMBILAN KEPUTUSAN SOSIAL BAGI SISWA SMP - Arif Ainur Rofiq (Psympathic : Jurnal Ilmiah Psikologi, 2015)
Social decision making skill is the ability to control self to be not easily influenced by social stimulus. This skill operated by using decision making steps include identifying problem, gathering information, doing verification, deciding alternatives solution, and choosing the best solution. This social decision making skill is very important for junior high school students because the inability of adolescents in decision making might bring them to negative life stream, which leads to failure to achieve an integral personality. By that, the social decision making skill is an important competence to be mastered by